Entrepreneurship Education and Self-Efficacy: How Do They Affect the Entrepreneurial Readiness of Vocational Students? - Widati, Sekar Tri; Siti Neno Muawiyah; Suparno (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
The dearth of entrepreneurial activity in Indonesia can be attributed to the lack of requisite skills possessed by those who aspire to become entrepreneurs. It is evident that aspiring entrepreneurs lack the necessary skills to play an effective role in the country’s economy. Consequently, it is of the utmost importance to implement tangible measures with the objective of enhancing the country’s economic performance. In addition, it is essential to implement concrete measures with the aim of improving entrepreneurial skills among the population. One potential avenue for improvement is through educational initiatives that impart the requisite skills. The objective of this study is to assess the influence of entrepreneurial readiness on students from an early age. This study examines the effect of entrepreneurship education and self-efficacy on the entrepreneurial readiness of vocational students. The data utilized in this study were collected from primary sources. The data were processed using the structural equation modeling (SEM) partial least squares (PLS) version 4.0.2 application. The SEM-PLS Version 4.0.2 application demonstrated that entrepreneurship education has a significant effect on entrepreneurial intention. The findings indicate that entrepreneurship education plays a pivotal role in fostering vocational students’ readiness for entrepreneurship. The study found that self-efficacy has a significant effect on vocational students’ readiness for entrepreneurship. Furthermore, the results indicated that entrepreneurship education